2021
DOI: 10.1097/ana.0000000000000823
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electroencephalography Spectral Edge Frequency (SEF) and Patient State Index (PSI)-Guided Propofol-Remifentanil Anesthesia on Delirium After Laparoscopic Surgery: The eMODIPOD Randomized Controlled Trial

Abstract: Background: The effect of SedLine electroencephalography (EEG)-guided anesthetic care on postoperative delirium (POD) has not been studied.Methods: This single-center randomized EEG Monitoring tO Decrease the Incidence of Post-Operative Delirium (eMODI-POD) trial involved 1560 patients aged 50 years or above undergoing laparoscopic surgery. Propofol-remifentanil anesthesia was guided either by SedLine (EEG-guided care, n = 779) or not (usual care, n = 781). The goal of EEG-guided care was to maintain spectral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
(64 reference statements)
0
16
0
Order By: Relevance
“…Previous trials investigating the effect of pEEGguided general anesthesia on POD have also shown mixed results for efficacy. However, the incidence of POD in the trial by Wang et al 5 (1.1%) was much lower than the expected incidence in this surgical population (14%). While this lower than expected incidence of POD may have been related to their younger age, avoidance of benzodiazepines, use of propofol or an unknown characteristic of the Chinese population included in the study, the consequence of the low event rate is that the trial had limited power for testing clinically relevant differences between groups.…”
mentioning
confidence: 52%
See 4 more Smart Citations
“…Previous trials investigating the effect of pEEGguided general anesthesia on POD have also shown mixed results for efficacy. However, the incidence of POD in the trial by Wang et al 5 (1.1%) was much lower than the expected incidence in this surgical population (14%). While this lower than expected incidence of POD may have been related to their younger age, avoidance of benzodiazepines, use of propofol or an unknown characteristic of the Chinese population included in the study, the consequence of the low event rate is that the trial had limited power for testing clinically relevant differences between groups.…”
mentioning
confidence: 52%
“…Provision of information about protocol adherence is fundamental for appropriate interpretation of results. Fortunately, Wang et al5 provided this information; 8 summary statistics of pEEG adherence are reported. Although 2 parameters (SEF left >15 and SEF left/right >15) were statistically different, total propofol dose was similar between groups (median [interquartile range], 900 [600 to 1320] vs. 1000 [600 to 1350] mg in the pEEG-guided and usual care groups, respectively).…”
mentioning
confidence: 99%
See 3 more Smart Citations